2014
DOI: 10.1113/expphysiol.2014.080556
|View full text |Cite
|
Sign up to set email alerts
|

Increased cardiac output contributes to the development of chronic intermittent hypoxia‐induced hypertension

Abstract: New Findings r What is the central question of this study?Chronic intermittent hypoxia (CIH)-induced hypertension is commonly believed to be a consequence of sympathetic nervous system hyperactivity, but direct recordings of chronic vasoconstriction have never been performed hitherto. We determined whether chronic vasoconstriction contributes to the development of hypertension in CIH-exposed animals. r What is the main finding and its importance?We found no evidence of chronic vasoconstriction in CIH-exposed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 48 publications
8
32
0
Order By: Relevance
“…Lucking et al . () support their conclusion with the finding that baseline hindlimb vascular conductance was not altered by CIH. Furthermore, hexamethonium caused similar vasodilatation in the hindlimbs of control rats and those exposed to 2 weeks of CIH, suggesting no difference in sympathetic vasoconstrictor tone.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Lucking et al . () support their conclusion with the finding that baseline hindlimb vascular conductance was not altered by CIH. Furthermore, hexamethonium caused similar vasodilatation in the hindlimbs of control rats and those exposed to 2 weeks of CIH, suggesting no difference in sympathetic vasoconstrictor tone.…”
supporting
confidence: 64%
“…Additional findings made by Lucking et al . () may explain this paradox. Chronic intermittent hypoxia enhanced the elastin content and increased the compliance of the aorta, which should help to buffer rises in ABP caused by peripheral vasoconstriction.…”
mentioning
confidence: 99%
“…Additionally, there is growing literature about the prevalence of chronic obstructive pulmonary disease (COPD) in patients with CKD (11,12). Notwithstanding etiology, hypoxemia and hypoxia are associated with a host of acute and chronic sequelae affecting multiple organ systems (13)(14)(15), including the cardiovascular system (16,17), wound healing (18), proinflammatory pathways (19), and the central nervous system (20). Some of these pathologies are highly prevalent in patients on hemodialysis (for example, inflammation and changes in vascular smooth muscles and endothelium, processes that accelerate arteriosclerosis) (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Rodent models of long-term intermittent hypoxia have demonstrated hypertension and increased sympathetic activity (22), increased right ventricular systolic pressure, right ventricular mass, neovascularization of distal pulmonary vessels (23), systemic and pulmonary vascular pressure (24,25), cardiac hypertrophy, and cardiac and perivascular fibrosis (26). Previous studies in children have however not found a strong link between arterial desaturation and elevated HR and BP (27).…”
Section: Repetitive Respiratory Events In Childrenmentioning
confidence: 95%